Time-To-Build and Convex Adjustment Costs - Koeva Brooks, Petya (IMF Working Papers; Working Paper, 2001)
This paper incorporates time-to-build into the standard investment model with convex adjustment costs. The empirical Euler equation is estimated using a U.S. firm-level panel from Compustat. In spite of the introduction of time-to-build, the magnitude of the implied adjustment costs is unrealistically high. Exploiting another approach, I test directly the restrictions imposed by time-to-build on the investment equation. The results indicate that these restrictions cannot be rejected for five of the sixteen industries in the sample. Finally I show that time-to-build can explain approximately one-third of the variation in persistence of structure investment across four-digit industries.